Density‐independent prey choice, taxonomy, life history, and web characteristics determine the diet and biocontrol potential of spiders (Linyphiidae and Lycosidae) in cereal crops. Issue 3 (13th December 2021) - Cuff, Jordan P.; Tercel, Maximillian P.T.G.; Drake, Lorna E.; Vaughan, Ian P.; Bell, James R.; Orozco‐terWengel, Pablo; Müller, Carsten T.; Symondson, William O.C.
Abstract: Spiders are among the dominant invertebrate predators in agricultural systems and are significant regulators of insect pests. The precise dynamics of biocontrol of pests in the field are, however, poorly understood. This study investigates how density‐independent prey choice, taxonomy, life stage, sex, and web characteristics affect spider diet and biocontrol. We collected spiders in four genera of Linyphiidae (i.e., Bathyphantes, Erigone, Tenuiphantes, and Microlinyphia ), and individuals from the Lycosidae genus Pardosa, and their proximate prey communities from barley fields in Wales, UK between April and September 2018. We analyzed the gut contents of 300 individual spiders using DNA metabarcoding. From the 300 spiders screened, 89 prey taxa were identified from 45 families, including a wide range of pests and predators. Thrips were the dominant prey, present in over a third of the spiders sampled, but a type IV functional response appears to reduce their predation at peak abundances. Spider diets significantly differed based on web characteristics, but this depended on the genus and sex of the spider and it was not the principal separating factor in the trophic niches of linyphiids and lycosids. Diets significantly differed between spider genera and life stages, reflected in different propensities for intraguild predation and pest predation. Adult spiders predated a greater diversity of other predators, and juveniles predated a greater diversity of pests. Overall, Tenuiphantes spp. and Bathyphantes spp. exhibited the greatest individual potential for biocontrol of the greatest diversity of pest genera. The greater trophic niche complementarity of Pardosa spp. and Erigone spp., however, suggests that their complementary predation of different pests might be of greater overall benefit to biocontrol. Sustainable agriculture should aim to optimize conditions throughout the cropping cycle for effective biocontrol, prioritizing provision for a diversity of spiders which predate a complementary diversity of pest species. Abstract : Spiders are among the dominant invertebrate predators of cereal crops, but little is known about their prey choice or dietary variation and how they vary in terms of benefit to biocontrol. This study analysed the diet and prey choice of 300 spiders from cereal crops and found large disparities in biocontrol and intraguild predation between genera, sexes, life stages and web characteristics based on different prey preferences and prey‐specific functional responses.